Spatial Variability of Soil Inherent Fertility Status at Irrigation Rice Field in Waeapo Plain, Buru Regency - Susanto, Andriko Noto (JOURNAL OF TROPICAL SOILS, 2013)
Analysis and interpretation of spatial variability soils properties are a basis in site-specific nutrients management. Evaluation inherent potentiality (IP) of soil fertility status is the method to know variability of soil fertility and spatial distribution at the area. Evaluation of IP was conducted by mathematical calculation to eleven soil properties namely total C, total N, N-NH4+, total P, P-Bray 1, P (extract HCl 25%), [Ca+Mg]-exch., K-exch., CEC, available Si, and sand content. Result of IP evaluation in Waeapo plain indicated that from the total rice field area of 25,848.83 ha, 75.64% or 19,552.44 ha showed very low IP class, and the rest for the width of 6,296.39 ha or 24.36% had low IP class. Content of C-total, N-total, N-NH4+, P2O5 total, P2O5 extracted by HCl 25%, available P2O5 and Si was not limited IP, because they were all classified as moderate class. Limiting factor of very low and low IP was a combination of three elements of [Ca+Mg]-exch., K-exch, and CEC. Increasing CEC and availability of K with addition of ameliorant such as organic materials, calcite, zeolite and dolomite would improve IP status class.Keywords: Buru Island, inherent potentiality of soil fertility, rice, Waeapo Plain[How to Cite: Susanto AN and BH Sunarminto. 2013.Spatial Variability of Soil Inherent Fertility Status at Irrigation Rice Field in Waeapo Plain, Buru Regency. J Trop Soils 18 (2): 115-124. Doi: 10.5400/jts.2013.18.2.115][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.115] REFERENCESAl-Jabri M. 2008. Kajian metode penetapan kapasitas tukar kation zeolit sebagai pembenah tanah untuk lahan pertanian terdegradasi. J Standardisasi 10: 56-63  (in Indonesian). Davatgar N, Neishabouri MR, Sepaskhah AR. 2012. Delineation of site specific nutrient management zones for a paddy cultivated area based on soil fertility using fuzzy clustering. Geoderma 173: 111-118.Doberman A and T Fairhurst. 2000.  Rice: Nutrient disorders and nutrient management. International Rice Research Institute (IRRI).  Philippines. 191p. Dobermann A, C Witt, S Abdulrachman, HC Gines, R Nagarajan, TT Son, PS Tan, GH Wang, NV Chien, VTK Thoa, CV Phung, P Stalin, P Muthukrishnan, V Ravi, M Babu, GC Simbahan and MAA Adviento. 2003. Soil fertility and indigenous nutrient supply in irrigated rice domains of asia.  Agron J 95: 913-923.Esington ME. 2003. Soil and Water Chemistry. An Integrative Approach. CRC Press. Boca Raton - Florida. 523p.Fairhurst T,  A Dobermann, AG Quijano and V Balasubramanian. 2007. Kahat dan Keracunan Mineral dalam  Padi: Panduan Praktis Pengelolaan Hara, In : Fairhurst, C. Witt, RJ. Buresh, and A. Dobermann (Eds.). International Rice Research Institute (IRRI), International Plant Nutrition Institute (IPNI), and International Potash Institute (IPI). Diterjemahkan oleh Adi Wiyono. Badan Litbang Pertanian. Jakarta. 91p + A-46p  (in Indonesian).Haefele SM and MCS Wopereis. 2005. Spatial variability of indigenous supplies for N, P and K and its impact on fertilizer strategies for irrigated rice in West Africa. Plant  Soil 270: 57-72.Haefele SM, DE Johnson, S Diallo, MCS Wopereis and I Janin. 2000.  Improved soil fertility and weed management is profitable for irrigated rice farmers in the Sahel. Field Crops Res 66: 101-113.Hanudin E. 2000. Pedoman Analisis Kimia Tanah. Jurusan Tanah. Fakultas Pertanian. Universitas Gadjah Mada. Yogyakarta (in Indonesian).Hazelton P and B Murphy. 2007. Interpreting Soil Test Results. What Do All The Numbers Mean?. CSIRO Publishing.  Australia. 152p.Kyuma K. 2004. Paddy Soil Science. Kyoto University Press and Trans Pacific Press. 290p.  Mc Bratney AB and MJ Pringle. 1997. Spatial variability in soil-implication for precision agriculture. In: JV Stafford (ed.) Precision Agriculture ‘97. Vol. I. Bioss Scientific Publ. Ltd., Oxford, United Kingdom, pp.3-31.Meunier A.  2005. Clays. Springer-Verlag Berlin Heidelberg. Germany. 467p.N Davatgar, MR Neishabouri and AR Sepaskhah. 2012.  Delineation of site specific nutrient management zones for a paddy cultivated area based on soil fertility using fuzzy clustering. Geoderma 173-174: 111-118.Nguyen BV, DC Olk and KG Cassman. 2004.  Characterization of Humic Acid Fractions Improves Estimates of Nitrogen Mineralization Kinetics for Lowland Rice. Soils. Soil Sci. Soc. Am. J. 68: 1266-1277.Poerwadi AD and A Masduqi. 2004. Penurunan Kadar Besi oleh Media Zeolit Alam Ponorogo Secara Kontinyu. JPurifikasi 5: 169-174  (in Indonesian).Prasetyo BH and RJ Gilkes. 1997. Properties of Kaolinit from Oxisol and Alfisols in West Java.  Agrivita  20: 220 - 227.Sirappa MP, AN Susanto, AJ Rieuwpassa, ED Waas and S Bustaman. 2005. Karakteristik, Jenis Tanah dan Penyebarannya Pada Wilayah Dataran Waeapo,  Pulau Buru. Agriplus  15(1): 20-32 (in Indonesian).Sulaeman, Suprapto dan Eviati. 2005. Analisis Kimia Tanah, Tanaman, Air  dan Pupuk. Edisi Pertama. Balai Penelitian Tanah. Bogor. 136p (in Indonesian).Syam T. 2010. Spatial Variability of Soil Nutrients Content Related to Rice Yield. J. Trop Soils  15: 153-157.Tan KH. 2003. Humic Matter in Soil and The Environment. Principles and Controversies. Marcel Dekker, Inc. New York. 370p.Tan KH. 1993.  Principles of Soil Chemistry, 2nd ed. Marcel Deckker Inc., New York. 376p. Tesfahunegn GB, L Tamene and PLG Vlek. 2011.  Catchment-scale spatial variability of soil properties and implications on site-specific soil management in northern Ethiopia. Soil Till Res 117: 124-139.WEI, Yi-chang, You-lu BAI, Ji-yun JIN, Fang ZHANG, Li-ping ZHANG, Xiao-qiang LIU. 2009.  Spatial Variability of Soil Chemical Properties in the Reclaiming Marine Foreland to Yellow Sea of China.  Agric Sci China  8: 1103-1111.Witt C,  BT Yen, VM Quyet, TM Thu, JM Pasuquin, RJ Buresh and A Dobermann. 2007. Spatially Variable Soil Fertility in Intensive Cropping Areas of North Vietnam and Its Implications for Fertilizer Needs. Better Crops 91: 28-31.Yesrebi J, M Saffari, H Fathi, N Karimian, M Moazallahi and R Gazni. 2009. Evaluation and Comparison of Ordinary Kriging and Inverse Distance Weighting Methods for Prediction of Spatial Variability of Some Soil Chemical Parameters. Res  J Biol Sci 4:  93-102. Yoshida S. 1981. Fundamentals of  Rice Crop Science. IRRI. Los Banos, Philippines. 269p.